Imaginal Disc Growth Factor 6 (Idgf6) Is Involved in Larval and Adult Wing Development in Bactrocera correcta (Bezzi) (Diptera: Tephritidae) - Zhao, Yan; Li, Zhihong; Gu, Xinyue; Su, Yun; Liu, Lijun (Frontiers in Genetics, 2020)
In insects, imaginal disc growth factors (IDGFs), an important component of the glycoside hydrolase 18 (GH18) family of chitinases, have been reported to be associated with the maintenance of the cuticle and molting. However, there is little knowledge of their function. In this study, imaginal disc growth factor 6 (Idgf6), which is an Idgf, was first identified and cloned from the guava fruit fly Bactrocera correcta (Bezzi) (Diptera: Tephritidae), one of the most serious pest insects in South China and surrounding Southeast Asian countries. This gene encodes IDGF6 protein with a conserved domain similar to ChiA chitinases, the glycoside hydrolase 18 (GH18) family of chitinases, according to NCBI BLAST. Phylogenetic analysis indicated that all Idgf6s were highly conserved among similar species. Subsequent temporal expression profiling revealed that Idgf6 was highly expressed in both the late-pupal and mid-adult stages, suggesting that this gene plays a predominant role in pupal and adult development. Furthermore, RNA interference experiments against Idgf6 in B. correcta, which led to the specific decrease in Idgf6 expression, resulted in larval death as well as adult wing malformation. The direct effects of Idgf6 silencing on B. correcta indicated its important role in development, and Idgf6 might be further exploited as a novel insecticide target in the context of pest management.